Implementation of Student Worksheets (LKS) Using the Treffinger Model as A Guide For Self-Learning on Hydrocarbon Compound - Triliyansi, Triliyansi; Anggraini, Maya Erliza; Abudarin, Abudarin (J-PEK (Jurnal Pembelajaran Kimia), 2024)
This study demonstrates the Treffinger model's impact on autonomous learning through Student Worksheets (LKS) concerning hydrocarbon compounds. Students showed a good understanding of hydrocarbons through problem-solving using the Treffinger model, achieving an average score of 79.56. Implementing the Treffinger model in learning activities significantly enhanced their knowledge about Hydrocarbons, achieving a coefficient of 84.46%. Treffinger's learning paradigm enhances student engagement, innovation, active participation, and a student-centred approach, augmenting motivation, problem-solving, and critical thinking skills.